(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Government of India has taken wonderful activities to ensure Children and their individual rights as per the rules of UNO and other International Organizations exceptionally working for the welfare of children i.e. UNICEF. The Children’s Code Bill 2000 accommodates the constitution of a National Commission for Children for the better insurance of child rights and for advancing the best interests of the child inside the bigger setting of elevating and transferring qualities to fortify the family, society and the nation. Under the Bill ’Child rights’ methods and incorporates the rights identifying with survival, insurance, development, and support as elaborated in the Convention on the Rights of the Child 1989 and the Constitution of India. The Code Bill announces the UNCRC as consented by the Government of India to be a piece of the law of India and enforceable by every one of the courts in India. The Bill makes it an obligation and the duty of the government to regard and guarantee that the rights of the child are ensured and guaranteed to each child inside the region of India, independent of nationality, race, shading, sex, religion, language, birth, political or other feeling, ethnic, economic or social status, or property or disability. The Bill urges that each child ought to be ensured against all types of discrimination, misuse, punishment, or maltreatment on any ground. At present, government has taken promise for proceeding with new activities to improve the kind state of this powerless gathering from abuse for sheltered and secure future.